Effect of Food-fodder Farming on Sustainable Resources Use and Carbon Dynamics in Rainfed Semi-arid Tropics of India. Issue 18 (11th October 2021) - Kumar, Sunil; Kiran Kumar, T.; Singh, Jitendra Bahadur; Prasad, Mahendra; Ghosh, Probir Kumar
ABSTRACT: Soil organic carbon (SOC) is highly sensitive to land use change and helps in maintaining soil quality. Changes in soil fertility status, SOC dynamics, and carbon indices were studied in a four-year experiment with nine sets of food-fodder cropping systems (CS) and three resource conservation techniques like rainfed (RC1), life saving irrigation (RC2) and in-situ moisture conservation practices (RC3). Results showed that the CS5 [Tri-Specific Hybrid (TSH) + Desmanthus virgatus + (Sorghum + Cowpea – Chickpea)] recorded the highest values 12.25 g kg −1, 41.5 mg kg −1, 3.5 g kg −1, 289.5 mg kg −1, 424.8 µg g −1 soil, 54.69% and 39.31% of total carbon (TC), hot water-soluble carbon (HWSC), particulate organic carbon (POC), labile carbon (LC), soil microbial biomass carbon (SMBC), humic acid carbon (HA-C) and fulvic acid carbon (FA-C), respectively. Among resources conservation practices, RC3 improved the SOC (56.16%) and other carbon fractions significantly as compared to RC1. Significant and positive correlations ( P < 0.05) were found between carbon pools and available nutrients. The carbon management index (CMI) was also maximum (193) with CS5 and CS9 [TSH + Sesbania sesban + (Sorghum + Cowpea – Barley)] and RC3 (232). Therefore, promoting cultivation of food-fodder system with in-situ moisture conservation practices is considered as sustainable management option for sequester more carbon, sustainability and soil quality in rainfed semi-arid ecosystem.